Two-to-Two Processes at an Electron-Muon Collider - Bouzas, Antonio O.; Larios, F. (Advances in High Energy Physics, 2022)
Based on a recent proposal to build an electron-muon collider, we study two-to-two production processes e−μ+⟶ff¯, γγ that originate from dimension 6 and 8 operators. We compare the sensitivity to those effective couplings obtained at the collider with that of low energy measurements of μ⟶eγ, μ⟶ee¯e, and μ⟶e conversion that have recently been reported in the literature. Whereas for the production of first family fermions, the sensitivity of the collider processes is much weaker; for the second and third family fermions, it is similar or stronger than that of low-energy processes. In the case of e−μ+⟶γγ, the sensitivity to a dimension 8 contact operator turns out to be the strongest in comparison.